Aclonifen targets solanesyl diphosphate synthase, representing a novel mode of action for herbicides. Issue 10 (27th February 2020) - Kahlau, Sabine; Schröder, Florian; Freigang, Jörg; Laber, Bernd; Lange, Gudrun; Passon, Daniel; Kleeßen, Sabrina; Lohse, Marc; Schulz, Arno; von Koskull‐Döring, Pascal; Klie, Sebastian; Gille, Sascha
Abstract: BACKGROUND: Aclonifen is a unique diphenyl ether herbicide. Despite its structural similarities to known inhibitors of the protoporphyrinogen oxidase (e.g. acifluorfen, bifenox or oxadiazon), which result in leaf necrosis, aclonifen causes a different phenotype that is described as bleaching. This also is reflected by the Herbicide Resistance Action Committee (HRAC) classification that categorizes aclonifen as an inhibitor of pigment biosynthesis with an unknown target. RESULTS: A comprehensive Arabidopsis thaliana RNAseq dataset comprising 49 different inhibitor treatments and covering 40 known target pathways was used to predict the aclonifen mode of action (MoA) by a random forest classifier. The classifier predicts for aclonifen a MoA within the carotenoid biosynthesis pathway similar to the reference compound norflurazon that inhibits the phytoene desaturase. Upon aclonifen treatment, the phytoene desaturation reaction is disturbed, resulting in a characteristic phytoene accumulation in vivo . However, direct enzyme inhibition by the herbicide was excluded for known herbicidal targets such as phytoene desaturase, 4‐hydroxyphenylpyruvate dioxygenase and homogentisate solanesyltransferase. Eventually, the solanesyl diphosphate synthase (SPS), providing one of the two homogentisate solanesyltransferase substrate molecules, could be identified as the molecular target of aclonifen. Inhibition was confirmed using biochemical activity assays for the A. thaliana SPSs 1 and 2. Furthermore, a Chlamydomonas reinhardtii homolog was used for co‐crystallization of the enzyme–inhibitor complex, showing that one inhibitor molecule binds at the interface between two protein monomers. CONCLUSION: Solanesyl diphosphate synthase was identified as the target of aclonifen, representing a novel mode of action for herbicides. © 2020 Society of Chemical Industry Abstract : This article reports the identification of solanesyl diphosphate synthase (SPS) as the molecular target of the herbicide aclonifen. SPS is involved plastoquinone‐9 (PQ‐9) biosynthesis, which represents an important co‐factor for phytoene desaturation. Therefore, SPS inhibition explains the observed phytoene accumulation in aclonifen treated plants. Identification of SPS as target represents a novel mode of action for herbicides. © 2020 Society of Chemical Industry